2018
DOI: 10.3390/met8121024
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Formation Mechanism of Inclusions in 304L Stainless Steel during the VOD Refining Process

Abstract: The formation and characteristics of non-metallic inclusions in 304L stainless steel during the vacuum oxygen decarburization (VOD) refining process were investigated using industrial experiments and thermodynamic calculations. The compositional characteristics indicated that two types of inclusions with different sizes (from 1 μm to 30 μm) existed in 304L stainless steel during the VOD refining process, i.e., CaO-SiO2-Al2O3-MgO external inclusions, and CaO-SiO2-Al2O3-MgO-MnO endogenous inclusions. The calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The review papers focus on the state of the art and perspectives in repairing and reinforcing historic timber structures by stainless steels [1], on duplex and super-duplex stainless steel microstructures and the evolution of their properties by surface modification processes [2], on the process and properties of reversion-heated austenitic stainless steels [3] and on the 3D printing of stainless steels by the laser powder bed fusion technique [4]. A group of research papers deal with physical metallurgy and advancedcharacterization techniques [5], others with process aspects [6][7][8] or property application items related to stainless steels [9][10][11][12][13][14]. The paper by Fava et al [5] presents and discusses the results of mechanical spectroscopy tests carried out on Cr martensitic steel.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review papers focus on the state of the art and perspectives in repairing and reinforcing historic timber structures by stainless steels [1], on duplex and super-duplex stainless steel microstructures and the evolution of their properties by surface modification processes [2], on the process and properties of reversion-heated austenitic stainless steels [3] and on the 3D printing of stainless steels by the laser powder bed fusion technique [4]. A group of research papers deal with physical metallurgy and advancedcharacterization techniques [5], others with process aspects [6][7][8] or property application items related to stainless steels [9][10][11][12][13][14]. The paper by Fava et al [5] presents and discusses the results of mechanical spectroscopy tests carried out on Cr martensitic steel.…”
Section: Contributionsmentioning
confidence: 99%
“…After that, the characteristics of the inclusions, such as morphology, size, number, and composition, are investigated by using a scanning electron microscope in combination with energy-dispersive X-ray spectroscopy. Chen et al [7] report the formation and characteristics of non-metallic inclusions in 304L stainless steel during the vacuum oxygen decarburization refining process, using industrial experiments and thermodynamic calculations. The compositional characteristics indicated that two types of inclusions with different sizes (from 1 to 30 µm) existed in 304L stainless steel during the refining process, i.e., CaO-SiO2-Al2O3-MgO external inclusions, and CaO-SiO2-Al2O3-MgO-MnO endogenous inclusions.…”
Section: Contributionsmentioning
confidence: 99%
“…The results show that the inclusion mainly includes Mg, Al, and O. The inclusions in the stainless steel were brought into the production process and the deoxidation process through mixing [31]. Al, as a strong oxidation metal, is the common deoxidant used in the production process of steel [32].…”
Section: Surface Characteristic Depended On the Acidification Durationmentioning
confidence: 99%
“…Chen et al analyzed the process of inclusion collision and growth removal, and considered the influence of gas bubbles in the formation model. However, the influence factors of inclusions adsorbing RH refractory material walls were neglected [13]. e model also did not meet the overall mass conservation of inclusions, and did not consider the distribution of inclusions in RH flow field [14].…”
Section: Introductionmentioning
confidence: 99%